The Impact of Spine Injuries on Amateur Athletes: An Exploratory Analysis of Sport-Related Patient-Reported Outcomes - Philipp Raisch; Tabea Hirth; Michael Kreinest; Sven Y. Vetter; Paul A. Grützner; Matthias K. Jung (MDPI AG, 2024)
Introduction: There is a lack of information on return to sport and patient-reported outcome measures (PROMs) in amateur athletes after isolated spine injuries. Methods: A single-center cohort study in amateur athletes aged 18 to 60 with isolated spine injuries; clinical data collection and follow-up via telephone interview and standardized PROMs (Short-Form 36, Oswestry and Neck Disability Index, Tampa Scale of Kinesiophobia, Hospital Anxiety and Depression Scale, Pain Visual Analog Scale). Bivariate analyses of potential influencing factors on PROMs were conducted using the Wilcoxon Signed-Rank Test. p-values < 0.05 were considered statistically significant. Results: Out of the 80 included participants, 78% (n = 62) were active in sport at follow-up. PROMs were slightly worse than those described for the age-adjusted general population. There were consistent associations of better PROMs with having reached the subjective preinjury level of performance in sport, while injury severity and surgical or conservative therapy did not show consistent associations with PROMs. Conclusion: Most amateur athletes resume their sports activity after a spine injury. Better outcomes are associated with individuals' resumption of sport and subjective level of performance, while injury severity and surgical or conservative therapy do not show consistent associations with PROMs, highlighting the importance of patient education, rehabilitation, and encouragement.